The problematic Hebrew word ‘ועבר’ Nahum 1:12: The study of ancient translations - Philip S. Chia (Verbum et Ecclesia, 2025)
What is the meaning of ‘ועבר’ found in Nahum 1:12? The textual tradition is divided. The Septuagint (LXX) omits this Hebrew word, while the Vulgate translates literally as ‘et pertransibit’ in Nahum 1:12. Although the Peshitta has a similar translation with the Masoretic text and the Vulgate, it differs on the subject: they will go through or ‘ܘܥܒܪܘ’. Targum, on the other hand, interprets the Hebrew word as ‘ויעברון על פרת ית’ or ‘they passed on the Euphrates’. This disagreement raises important questions about the original wording of the verse, its interpretation and the sources of the various readings that emerged during its transmission.